Passively q-switched erbium-doped fiber laser using side-polished fiber and 2D materials as saturable absorbers / Hazirah Hassan - Hazirah , Hassan (2019)
Technology and applications of fiber optics have progressed rapidly in recent years. Fiber optics sensor has been commercialized successfully and well established in various industries ranging from biomedical to defense technologies. Passively Q-switching technique is suitable to obtain short and powerful pulse. For this technique, saturable absorber (SA) is an important device and has experienced rapid development from semiconductor-base to nano-sheet materials base. Eventhough passively Q-switched fiber lasers usually have very simple structures with SA placed inside the laser cavity, the repetition frequency depends on many other operations parameters. As for the side-polished fiber (SPF), the fiber side-cladding is removed to expose the core for the purpose of coating SA on its surface. This is to ensure the laser evanescent wave will interact with the SA due to the difference in refractive index between SA with its surrounding. SPF has a unique structure which the cladding is literally removed until reaching to the core so that the sensitivity of the SPF can be improved. This thesis also focuses on the Molybdenum disulfide (MoS2) material which is one of the transition-metal dichalcogenides that is used as saturable absorber. MoS2 has a unique characteristics because when it is in monolayer form, it becomes a direct bandgap of ~1.9 eV however when it is in multilayer forms, it will have indirect bandgap. In addition to that, Carbon Platinum (CPt) is also proposed as SA in this thesis. CPt is a new material that was used as SA to produce Q-switched fiber laser. CPt which in liquid form with volume of 25 μL is dropped onto the SPF using micro-pipette and it take 30 minutes to dry.